Current issues in diagnostic breast pathology. Issue 9 (19th July 2012) - Walker, Rosemary A; Hanby, Andy; Pinder, Sarah E; Thomas, Jeremy; Ellis, Ian O; ,
Abstract : On behalf of the NHS Breast Screening Programme Pathology Coordinating Group we present recommendations for terminology and diagnostic criteria for a number of key areas of practice in breast pathology where terminology can be confusing and where accurate communication will ensure appropriate clinical management. These recommendations cover columnar cell lesions and the spectrum of changes that can be seen in these epithelial proliferations, lobular neoplasia, micrometastases and isolated tumour cells in axillary lymph nodes, the use of basal/myoepithelial markers in diagnostic practice and oestrogen receptor testing in ductal carcinoma in situ.